2008
DOI: 10.1016/j.jpeds.2008.05.059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Congenital Heart Defects in Metropolitan Atlanta, 1998-2005

Abstract: Objective-To determine an accurate estimate of the prevalence of congenital heart defects (CHD) using current standard diagnostic modalities.Study design-We obtained data on infants with CHD delivered during 1998-2005 identified by the Metropolitan Atlanta Congenital Defects Program, an active, population-based birth defects surveillance system. Physiologic shunts in infancy and shunts associated with prematurity were excluded. Selected infant and maternal characteristics of the cases were compared with those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
638
9
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,068 publications
(734 citation statements)
references
References 16 publications
43
638
9
11
Order By: Relevance
“… Maternal diabetes mellitus; The study by Correa et al found odds ratios for pregestational diabetes mellitus (PGDM) and all cardiac defects was 4.64 (2.87-7.51), while gestational diabetes mellitus (GDM) was associated with cardiac defects found 1.59 (1.27-1.99) (Correa et al, 2008). This excess risk is related to the level of maternal hyperglycemia during the embryonic period.…”
Section: Maternal Health and Medical Diseasementioning
confidence: 99%
“… Maternal diabetes mellitus; The study by Correa et al found odds ratios for pregestational diabetes mellitus (PGDM) and all cardiac defects was 4.64 (2.87-7.51), while gestational diabetes mellitus (GDM) was associated with cardiac defects found 1.59 (1.27-1.99) (Correa et al, 2008). This excess risk is related to the level of maternal hyperglycemia during the embryonic period.…”
Section: Maternal Health and Medical Diseasementioning
confidence: 99%
“…This group of diseases affects social and productive life by intervening in the planning and economy of the health system, as well as increased costs and productive force in the country 4 .…”
Section: Anomalies Of Intestinal Nervous Plexus Includingmentioning
confidence: 99%
“…With a prevalence of approximately 8 per 1000 births, cardiac anomalies are the most common birth defects (Hoffman and Kaplan, 2002;Reller et al, 2008); they appear as isolated defects, but also occur frequently in children with genetic or other syndromes. Teratogenic effects will most likely not cause an increase in all birth defects, but only in specific birth defects.…”
Section: Case Definitionmentioning
confidence: 99%